Pemerintahan Pada Masa Transisi Pergantian Kepala DaerahDalam Perspektif Otonomi Daerah - Abdul Azis Hasan (JURNAL AKTA YUDISIA, 2021)
Abstract  Two problem formulations were discussed in this study, namely the politics of law of governance in the transition period of the replacement of regional heads in Indonesia and the organizational design and governance work in the transition period of the replacement of regional heads in the perspective of regional autonomy. As a normative legal research, it used the statute and the conceptual approaches. Based on the results of the study it was concluded that the politics of law of regional governance in the transition period of the replacement of regional heads in Indonesia are partially regulated in Law Number 10 of 2016 where regional heads are prohibited from replacing officials 6 (six) months prior to the date of the nomination of candidate pairs up to the end of the term of office and 6 (six) months from the date of inauguration unless obtaining written approval from the Minister. Furthermore, in Regulation of the Minister of Home Affairs No. 86 of 2017, it is regulated that the formulation of vision, mission and program of candidates for regional head and deputy regional head must be guided by the RPJPD and if there is a time lag between the elections until the inauguration of the elected regional head exceeds a period of 6 (six) months, the draft the RPJMD technocracy can be refined by referring to the vision, mission, and program of the elected regional head. The implementation of the two regulations has the potential to violate the principles of regional government implementation, namely professionalism, public Intertest, and effectiveness. In order to minimize the potential violations of the principle of regional government implementation, it is necessary to revise Law Number 10 of2016 and Permendagri Number 86 of 2017. Keywords:  Regional  Government,  Transition  Period  Substitution  of  RegionalHeads, Transition